2020
DOI: 10.1007/s40268-020-00297-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Polyethylene Glycol (PEG) Levels Reach Steady State Following Repeated Treatment with N8-GP (Turoctocog Alfa Pegol; Esperoct®)

Abstract: Background Extended half-life (EHL) factor VIII (FVIII)-replacement therapies enable patients with haemophilia A to maintain higher activity levels with fewer injections. N8-GP (turoctocog alfa pegol; Esperoct ®) is an EHL product derived from conjugation of polyethylene glycol (PEG) to a recombinant FVIII protein. Upon activation, PEG is released from the active protein and excreted in urine and faeces. While PEG levels are expected to reach steady state with repeated dosing, there has been some discussion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…A follow-up study of the Phase IV with treatment time as long as 3 years in 644 patients was also investigated, and no obvious differences in the incidence of ARs and CNS-related ARs between the treatment groups were found. These data are consistent with other PEG-conjugated drug clinical trials, such as those conducted for 40 kDa PEG N9-GP (50,54,55) and 60 kDa PEG BAY 94-9027 (56). In a long-term safety study of N9-GP administered for at least 5 years in 25 children with hemophilia B from 17 sites in 8 countries, the mean PEG plasma reached a steady state after 6 months, and no new abnormal findings in neurological examinations were observed in the study (55).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A follow-up study of the Phase IV with treatment time as long as 3 years in 644 patients was also investigated, and no obvious differences in the incidence of ARs and CNS-related ARs between the treatment groups were found. These data are consistent with other PEG-conjugated drug clinical trials, such as those conducted for 40 kDa PEG N9-GP (50,54,55) and 60 kDa PEG BAY 94-9027 (56). In a long-term safety study of N9-GP administered for at least 5 years in 25 children with hemophilia B from 17 sites in 8 countries, the mean PEG plasma reached a steady state after 6 months, and no new abnormal findings in neurological examinations were observed in the study (55).…”
Section: Discussionsupporting
confidence: 90%
“…The calibration ranged from 0.1 to 10 mg/L in urine after a single intravenous administration of the PEGylated drug. LC-MS/MS was also applied to analyze the 40 kDa PEGylated drug N8-GP in rats and humans (50). Further exploration of Jintrolong ® is still needed to detect intact PEG and lower doses or metabolites of PEG.…”
Section: Discussionmentioning
confidence: 99%
“…However, hypothetical concerns have been raised regarding long‐term exposure to PEGylated drugs and the potential for PEG to accumulate beyond steady‐state levels in some tissues 27 . Recently, a study conducted by Novo Nordisk examined the plasma concentration of PEG in children, adolescents, and adults receiving long‐term prophylactic treatment with N8‐GP as part of the pathfinder program 28 . This study demonstrated that PEG levels reach steady state in plasma and do not accumulate further beyond expected steady‐state levels.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Interestingly, a closer examination of PEG exposure in patients treated with N8-GP for periods up to 5 years showed that plasma PEG levels rapidly achieved a steady state, with no unexpected increase above steady-state levels, even with long-term treatment. 10 PEG is ubiquitous and is used extensively in various consumer products, including commercial medicines. The attainment of a steady state is reassuring, as it demonstrates the ability of the body to excrete this moiety, confirming the long-term safety observed with other PEG molecules used in patients with chronic conditions.…”
mentioning
confidence: 99%